Front Cover: Helenalin Analogues Targeting NF‐κB p65: Thiol Reactivity and Cellular Potency Studies of Varied Electrophiles (ChemMedChem 4/2018). (20th February 2018) - Widen, John C.; Kempema, Aaron M.; Baur, Jordan W.; Skopec, Hannah M.; Edwards, Jacob T.; Brown, Tenley J.; Brown, Dennis A.; Meece, Frederick A.; Harki, Daniel A.
Abstract : The Front Cover shows two race cars, representing an endocyclic enone and an exocyclic methylene butyrolactone, racing to complete hetero‐Michael additions to a biological thiol. This work describes the synthesis of simplified helenalin analogues containing combinations of endocyclic enones and exocyclic methylene butyrolactones. Thiol reactivity kinetics and NF‐κB inhibitory activities of the simplified helenalin analogues is reported, which provides insights into the contributions of the individual electrophiles to biological potency. More information can be found in the Full Paper by Daniel A. Harki et al. onpage 303 in Issue 4, 2018 (DOI:10.1002/cmdc.201700752 ).